MCDM based Joint Admission Control for Heterogeneous Wireless Networks - Alkhawlani, Mohammed M. (IEEE, 2012)
Heterogeneous Wireless Network (HWN) is defined as a new type of wireless networks where anyone can communicate with anyone else, anywhere and anytime, or enjoy any service of any network operator, through any network of any service provider in the most efficient and optimal way according to the user criteria. The needs for supporting various applications and services and for providing ubiquitous coverage in the HWN require more complex and intelligent radio resource management techniques that enable the coordination among the different radio access technologies. This paper considers the most important radio resource management mechanism in HWN that is Joint Admission Control (JAC). JAC handles all new or handoff service requests in the HWN and checks whether the incoming service requests to be admitted. Then, it allocates the required resources and guarantees the QoS constraints for the service. This paper develops a VIKOR decision support system based algorithm to address the JAC problem in the modern HWN networks. The proposed algorithm aims to decrease the influence of the dissimilar, imprecise, and contradictory measurements for the JAC criteria coming from different sources. A performance analysis is done and the results are compared with traditional algorithms for JAC. These results demonstrate a significant improvement with our developed algorithm.